Stepwise approach to induce infrequent premature ventricular complex using bolus isoproterenol and epinephrine infusion. Issue 5 (6th April 2020) - Shinoda, Yasutoshi; Komatsu, Yuki; Nogami, Akihiko; Igarashi, Miyako; Yamasaki, Hiro; Sekiguchi, Yukio; Aonuma, Kazutaka; Ieda, Masaki
Abstract: Background: Paucity of a premature ventricular complex (PVC) during ablation procedures may occur and be associated with a lower success rate. Isoproterenol (ISP) injections are commonly used to induce PVC; however, the induced tachycardia sometimes prevents the appearance of PVC. Epinephrine (EPI) administration may be an alternative strategy to induce PVC due to its smaller effect on heart rate (HR). This study sought to examine the electrophysiological impact of EPI injection, with a stepwise induction protocol, for infrequent intraprocedural PVC. Methods: We studied 78 consecutive patients who underwent catheter ablation of idiopathic frequent PVC. If no PVC was observed at the beginning of the procedure, ISP (10 µg) was injected. If clinical PVC was not induced by ISP administration, EPI (10 µg) was injected. Results: Of 18 patients without PVC at baseline, ISP injection induced PVC in five patients. Of the remaining 13 patients, EPI injection successfully induced PVC in seven patients (53%). The maximum HR and increments of HR after EPI injection were significantly lower than those after ISP injection (99 ± 15 vs 137 ± 15 bpm, P  = .001; 22 ± 10 vs 53 ± 12 bpm, P  < .001, respectively). There were no complications related to the induction protocol. Conclusion: EPI injection following ISP injection is an effective and safe stepwise approach for the induction of infrequent PVC in the electrophysiology laboratory. It is hypothesized that α‐ and β‐adrenergic receptor stimulation by EPI injections, with reduced HR acceleration compared to that with ISP injections, may result in the successful induction of PVC.